2007
DOI: 10.2967/jnumed.106.039024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Diffusely Increased 18F-FDG Uptake in the Thyroid Gland

Abstract: Our purpose was to determine the clinical significance of diffusely increased 18 F-FDG uptake in the thyroid gland as an incidental finding on PET/CT. Methods: All patients who were found to have diffuse thyroid uptake on 18 F-FDG PET/CT in our institution between November 2004 and June 2006 were investigated and compared with an age-and sex-matched control group. The 18 F-FDG uptake in the thyroid was semiquantified using maximum standardized uptake value and correlated to the available serum thyroid-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 16 publications
12
83
0
2
Order By: Relevance
“…Diffuse thyroid uptake does not seem to be affected by hormone replacement therapy and thyroid function state. Karantanis et al found that patients receiving thyroxine therapy for primary hypothyroidism could demonstrate diffusely increased 18 F-FDG uptake in their thyroid gland [11]. In agreement, most (95.8%) of our study population had already started thyroid hormone replacement therapy after unilateral thyroid lobectomy, and the thyroid function status was not significantly different between the two groups.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Diffuse thyroid uptake does not seem to be affected by hormone replacement therapy and thyroid function state. Karantanis et al found that patients receiving thyroxine therapy for primary hypothyroidism could demonstrate diffusely increased 18 F-FDG uptake in their thyroid gland [11]. In agreement, most (95.8%) of our study population had already started thyroid hormone replacement therapy after unilateral thyroid lobectomy, and the thyroid function status was not significantly different between the two groups.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, Tateish et al recently found that 20% of breast cancer patients in their study population showed diffuse thyroid uptake in PET/CT, which was significantly greater compared to the results of previous studies [14]. Although the precise mechanism for diffuse thyroid uptake is still unknown, the possibility of lymphocytic infiltration or active fibrosis formation related to chronic thyroiditis has been suggested [10,11]. 18 F-FDG PET is a noninvasive whole body imaging technique used to evaluate many kinds of malignant tumors.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…검사 환자의 0.6-3.3% 정도로 보고되었으며 [8]- [11] 자가 면역 갑상선 질환(autoimmune thyroid disease)과 관련 있음을 보고하였다 [12]- [15] .…”
Section: F-fdg 갑상선 섭취 증가는 Pet/ctunclassified